2000
DOI: 10.1093/dnares/7.6.347
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Coding Sequences of Unidentified Human Genes. XIX. The complete Sequences of 100 New cDNA Clones from Brain Which Code for Large Proteins in vitro

Abstract: As an extension of our human cDNA project for accumulating sequence information on the coding sequences of unidentified genes, we here present the entire sequences of 100 cDNA clones of unidentified genes, named KIAA1673-KIAA1772, from three sets of size-fractionated cDNA libraries derived from human adult whole brain, hippocampus, and fetal whole brain. The average sizes of the inserts and corresponding open reading frames of cDNA clones analyzed here were 4.9 kb and 2.7 kb (corresponding to 895 amino acid re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 12 publications
5
76
0
Order By: Relevance
“…A large sequencing project first identified the coding sequence for fibrillin-3 in a human brain cDNA library (Nagase et al, 2001). Subsequently, Corson et al reported strong expression of fibrillin-3 in human fetal brain based on RT-PCR and Northern blotting (Corson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large sequencing project first identified the coding sequence for fibrillin-3 in a human brain cDNA library (Nagase et al, 2001). Subsequently, Corson et al reported strong expression of fibrillin-3 in human fetal brain based on RT-PCR and Northern blotting (Corson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The cDNA coding for fibrillin-3 has first been isolated from human fetal brain (Nagase et al, 2001). Corson and coworkers subsequently found that fibrillin-3, similar to fibrillin-2, is mainly expressed during embryonic development (Corson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Our observation of a frequent mutant allele LOH in the region telomeric to MLH1, in particular, implicated this region as a possible location of additional targets for LOH irrespective of MLH1. Potential target genes include DCAMKL3 (KIAA1765), which has doublecortin and CaM-kinase-like 3 motifs and may function in cell signaling (Nagase et al, 2000;Ohmae et al, 2006), and STAC (SRC homology 3 and cysteine-rich domain), which may play a role in cell proliferation, transformation and apoptosis (Suzuki et al, 1996;Satoh et al, 2006). The region at 3p21-22 is often deleted in human epithelial malignancies (Protopopov et al, 2003), and future studies should examine if DCAMKL3 or STAC, or other genes from this region, are directly involved in these tumorigenic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Production of the N-and C-terminal fragments of human fibrillin-1 (rFBN1-N, rFBN1-C, respectively) and fibrillin-2 (rFBN2-N, rFBN2-C, respectively) has been described in detail previously (Jensen et al, 2001;Lin et al, 2002). To produce a new recombinant C-terminal half of human fibrillin-3 (rFBN3-C; D 1321 -R 2684 ), the cDNA for human fibrillin-3 (clone KIAA1776, Nagase et al, 2001) was obtained from the Kazusa DNA Research Institute (Chiba, Japan) and cloned into the pBluescript II SK(ϩ) plasmid (Stratagene, La Jolla, CA). The resulting plasmid pBS-FBN3 was cut with NheI ϫ SgrAI and the 7888-base pair fragment was ligated with the complementary oligonucleotides 5Ј-CTAGCAGACCTGGATGAATGAATG-CATCTCCCAGGAGCA-3Ј and 5Ј-CCGGTGCTTGGGAGATGCATTCATC-CAGGTCTG-3Ј generating a NheI restriction site at the 5Ј end (pBS-rFBN3C-1).…”
Section: Proteinsmentioning
confidence: 99%